A case report of Gorham-Stout disease diagnosed during the course of recurrent meningitis and cholesteatoma - Makoto Hosoya; Naoki Oishi; Jun Nishiyama; Kaoru Ogawa (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Gorham-Stout disease is a rare bone disorder. Here, we present a case of Gorham-Stout disease diagnosed during follow-up of a patient with cholesteatoma; the disease affected the temporal bone and other sites of the skull. To the best of our knowledge, this is the first report of Gorham-Stout disease diagnosed with recurrent cerebrospinal leakage after surgery to treat cholesteatoma. Case presentation A 25-year-old male patient re-presented to our department for the first time in 7 years with otorrhea in the right ear and recurrent meningitis. The patient had a history of multiple surgeries for cholesteatoma and suffered from recurrent cerebrospinal fluid leakage, which initially was thought to be caused by recurrence of cholesteatoma. Therefore, skull base reconstruction was planned. However, the underlying cause was identified eventually as defects in the temporal bone caused by massive osteolysis due to Gorham-Stout disease. Skull base reconstruction was abandoned because the osteolysis was considered to be progressive. Conservative treatment with infectious control was implemented as an alternative. Conclusion This case describes unusual temporal bone osteolysis after cholesteatoma surgery and the importance of considering the possibility of multiple concurrent diseases in such individuals. The distinguishing features of this case are the fact that the temporal bone had disappeared, and deconstruction was complicated by infection and inflammation caused by cholesteatoma, surgical invasion, and Gorham-Stout disease. Appropriate diagnosis saved the patient from ineffective multiple surgeries for cerebrospinal fluid leakage or cholesteatoma, and improved his quality of life.